Judaization in Palestine: Is It Genocide According to the 1998 Rome Statute? - hafara khoirunisa; sefriani sefriani; jawahir thontowi; jaya indra santosa; yashifa febriani; Ahmed Zeiad Masoud (Faculty of Law, Sriwijaya University, Indonesia, 2024)
The purpose of this study is to analyse the act of genocide in the attempt at Judaization in Palestine based on the 1998 Rome Statute and examine the possibility of categorizing the Judaization of Palestine as cultural genocide because Judaization has changed various aspects of Palestinian life and the Palestinian territories themselves. In addition, cultural genocide has been eliminated from its history, but there are still actions that are assumed to lead to it. This research is a type of normative legal research using a conceptual, statutory, case, and historical approach. The results of this study indicate that the Judaization of land and people in Palestine is a crime of genocide, as stated in Article 6 (c) of the 1998 Rome Statute. At the same time, the Judaization of identity and holy places can be categorized as cultural genocide, according to experts. However, the opinions of experts contained in legal works are subsidiary legal sources and, until now, have not been recognized as customary international law. In addition, the Judaization of identity and holy places within the framework of international law can only be viewed as genocidal intent, not cultural genocide.